2016
DOI: 10.1002/oby.21562
|View full text |Cite
|
Sign up to set email alerts
|

Insulin access to skeletal muscle is impaired during the early stages of diet‐induced obesity

Abstract: Objective Insulin must move from the blood to the interstitium to initiate signaling, yet access to the interstitium may be impaired in cases of insulin resistance, such as obesity. We investigated whether consuming a short- and long-term high-fat diet (HFD) impairs insulin access to skeletal muscle, the major site of insulin-mediated glucose uptake. Methods Male mongrel dogs were divided into 3 groups consisting of control diet (n=16), short-term (n=8) and long-term HFD (n=8). Insulin sensitivity was measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
26
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 28 publications
6
26
1
1
Order By: Relevance
“…In this study, we found that a PUFA diet, although inducing a significant weight gain, did not induce insulin resistance or impair insulin movement into the interstitial space under basal insulin levels, as compared with the LARD diet. Our previously published results also demonstrate that a LARD diet induces insulin resistance and impairs insulin access to the skeletal muscle interstitium under basal, noninsulin stimulated conditions , but not during higher levels of exogenously infused insulin. Thus, the present results support the concept that PUFA diets do not have the detrimental effects on insulin action seen with saturated fatty acid diets, even in the context of comparable obesity.…”
Section: Discussionsupporting
confidence: 66%
“…In this study, we found that a PUFA diet, although inducing a significant weight gain, did not induce insulin resistance or impair insulin movement into the interstitial space under basal insulin levels, as compared with the LARD diet. Our previously published results also demonstrate that a LARD diet induces insulin resistance and impairs insulin access to the skeletal muscle interstitium under basal, noninsulin stimulated conditions , but not during higher levels of exogenously infused insulin. Thus, the present results support the concept that PUFA diets do not have the detrimental effects on insulin action seen with saturated fatty acid diets, even in the context of comparable obesity.…”
Section: Discussionsupporting
confidence: 66%
“…Previous studies have shown that insulin-stimulated MGU depends on the ability of insulin to cross this endothelial barrier (30). Furthermore, experiments in insulin-resistant subjects have shown that impaired insulin delivery is a feature of muscle insulin resistance (6)(7)(8), which is associated with type 2 diabetes. Therefore, characterizing the mechanism of capillary endothelial insulin transport is critical to understanding the progression of insulin resistance (31).…”
Section: Resultsmentioning
confidence: 99%
“…The ability of insulin to stimulate glucose uptake into SkM, the major site of insulin-stimulated glucose disposal, depends on the rate at which insulin traverses the endothelium (5). Furthermore, the delivery of insulin to SkM has been shown to be impaired in the setting of diet-induced insulin resistance (6)(7)(8). Despite the importance of transendothelial insulin efflux to insulin action and insulin resistance, the mechanism by which insulin transits the endothelium in SkM is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Most previous studies, but not all , have demonstrated that SkM insulin delivery is reduced in humans and animal models with obesity. SkM insulin delivery depends on the capillary surface area for insulin exchange and the rate of insulin movement across the endothelium.…”
Section: Discussionmentioning
confidence: 98%